Hadits sebagai Sumber Hukum Islam Menurut Orientalis - Anwar Rizqi; Hilali Basya; Lukmanul Hakim; Saiful Bahri; Sopa Sopa (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to determine Joseph Schacht’s thoughts on hadith as Islamic law and to determine the influence of Joseph Schacht’s thoughts on Islamic law. Schacht is one of the orientalists who has a significant influence in the study of Islamic studies, especially regarding the authenticity of hadith. He argues that most of the hadith circulating today are products of the second and third centuries of Hijriah, not directly from the Prophet Muhammad SAW. The research method used is a qualitative method with a historical-critical approach. The main data sources are the works of Joseph Schacht, especially his books and articles that discuss the status of hadith in Islamic law. This study also includes a literature review of the responses and criticisms of contemporary Islamic scholars towards Schacht’s views. The data are analyzed to identify Schacht’s main arguments, as well as how these views influence the methodology of modern Islamic law studies. The results of the study show that Schacht argues that hadith is more of a recording of an oral tradition that developed after the death of the Prophet Muhammad SAW. According to him, the process of collecting, distributing, and verifying hadith was often influenced by social and political factors at the time, raising doubts about the authenticity and reliability of hadith as a source of law. Its influence was not only limited to academics, but also influenced the public’s view of the importance of historical criticism in understanding the intellectual heritage of Islam. This study emphasizes the importance of a more critical and balanced approach in the study of Islamic law, which can help develop interpretations that are more relevant to contemporary demands and values.